Pemanfaatan QRIS sebagai Media Promosi dan Transaksi Pemasaran Digital UMKM - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The development of digital technology has brought significant changes to marketing and business transaction systems, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the utilization of the Quick Response Code Indonesian Standard (QRIS) as both a promotional medium and a transaction tool in digital marketing activities of MSMEs. The research employs a descriptive quantitative approach by distributing questionnaires to MSME owners who have adopted QRIS as a means of payment and promotion. The results indicate that the use of QRIS not only facilitates cashless transactions but also enhances the professional image and consumer trust toward MSMEs. Moreover, the integration of QRIS with social media and digital marketing platforms expands promotional reach and increases sales volume. This study confirms that QRIS plays a strategic role in strengthening the digital transformation of MSMEs through transaction efficiency and effective marketing communication.